Teachers' Reflections and Students' Perceptions of Blended Learning in Increasing English Learning Independence at Islamic High School - Usriya Tas'adina (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore the reflections of an English teacher and the perceptions of eleventh-grade students regarding the implementation of blended learning, with a specific focus on its impact on learner autonomy. It seeks to understand how this approach fosters independent learning and to identify the challenges encountered during its application in a secondary school context. A descriptive qualitative method was employed, involving the researcher as the English teacher and thirty purposively selected students from MAN 2 Ponorogo. Data were collected through the teacher’s written reflections, open-ended student questionnaires, and informal interviews to gain deeper insights into participants’ experiences. The data were analyzed using thematic analysis, involving systematic coding, categorizing, and interpreting emerging themes. Findings indicate that blended learning positively contributes to the development of learner autonomy. Students demonstrated enhanced time management, increased initiative in accessing learning resources, and a greater sense of responsibility for their learning progress. Nevertheless, several challenges were identified, particularly related to technological readiness, internet reliability, and time constraints faced by both students and the teacher. The study concludes that the successful implementation of blended learning requires carefully designed instructional strategies, sufficient technological infrastructure, and consistent institutional support to maximize its potential in promoting autonomous learning in the English classroom.